The Role of Nazhir in Overseeing The Settlement of Waqf Land Dispute - Novita, Della; Helim, Abdul; Supriadi, Akhmad (JURNAL EKONOMI SYARIAH, 2024)
AbstractIntroduction to The Problem: The waqf land disputes which occurred on Jl. Keranggan, Palangka Raya City with an area of 580,000 m2 occurred because of the inter-Nazhir case, where the old Nazhir brought the certificate of the donated land so that the new Nazhir could not carry out his duties optimally. Therefore, this study aims to determine and analyze the role of Nazhir in overseeing the settlement of waqf land disputes on Jl. Keranggan, Palangka Raya City.Design/Methodology/Approach: This field research used qualitative methods. There are 1 nazhir subjects and 2 informant. The data were collected through observations, interviews, and documentation. It applied source triangulation for data validation. The data analysis covered data collection, reduction, display, and concluding drawing.Findings: The result of this study is that the role of nazhir in over seeing the settlement of waqf land disputes has been role in carrying out their duties and obligations to care for and maintain the ridht to the waqf land, because the nazhir is the person who is responsible for maintain the rights to the waqf land, because the nazhir is the one who is responsible for the waqf land.Paper Type: Research Article or General ReviewKeywords: Dispute settlement, roles of nazhir